Integrating Women into Peacebuilding in the Democratic Republic of the Congo. A Case Study of Goma - Mbugua Henry, Salome Wairimu (Trinity College Dublin. School of Religion. Irish School of Ecumenics, 2021)
Lack of representation and participation of women in decision-making is a global phenomenon that has been under public discussion for many years. Feminist theory has articulated gender as an underlying factor in inequality, reinforced by patriarchy in societies where male domination continues in all public spheres. In the particular context of peacebuilding, the lack of representation and inclusion of women has been noted by the international community and UN Security Council Resolution (UNSCR) 1325 on Women, Peace and Security (UNSC, 2000) has become a cornerstone document advocating for women?s greater participation in peacebuilding. Moreover, theorists of peacebuilding, such as John Paul Lederach (1997), suggest that a whole-society, integrated approach to peacebuilding is necessary for sustainable peace. However, gender inequality continues to stymie such inclusive, integrated approaches. This study, set in the context of field research conducted in Goma, North Kivu province in DRC, explores the barriers to women?s participation in peacebuilding processes and their potential contributions. The study showed that against all the odds, local women activists are organising themselves and are speaking out about injustice and the impact of conflict on women and are leading discussions on peacebuilding at the community level. Through years of running their organisations and experiences of working with the community on the ground, these local woman leaders have accumulated important leadership skills. However, despite their commitment to peacebuilding efforts, they are excluded from formal peace meetings, even those held at the grassroots level. They face many challenges, given their patriarchal and conflict-ridden context, in terms of maintaining and sustaining their work, including a lack of resources and the fear of intimidation from male counterparts. Peacebuilding processes and discussions continue to be dominated and designed by men, while women continue to suffer the consequences of conflict. Applying Lederach?s theory of an integrated peacebuilding pyramid which argues for the importance of interactions between actors at three societal levels, (elite, civil society and grassroots actors), this thesis identifies potential avenues for integrating women in peacebuilding in the North Kivu region. The study posits that the integration of women in peacebuilding must be addressed by ensuring gender equality and addressing relations of power in each level of the pyramid.
APPROVED
Keywords: Peacebuilding; Gender Power Relations; United Nation Security Council; Women Participation; Sexual Violence; War, Conflict; UNSCR 1325; Equality; Peace and Security